LArterial Stiffness and its Related Factors in Patients on Hemodialysis - Yakar, Burkay; Demir, Mustafa; Onalan, Erhan; Kaya, Mehmet Onur (Coll Physicians & Surgeons Pakistan, 2021)
Objective: To evaluate the prevalence of arterial stiffness in patients on hemodialysis and related factors that aggravate the condition. Study Design: Prospective-cohort study. Place and Duration of Study: Department of Nephrology, Firat University Hospital, Turkey, from August to October 2019. Methodology: Central blood pressure (BP), augmentation index (AIx) and aortic pulse wave velocity score (PWVs) were assessed using the mobil-o-graph pulse wave velocity system. Increased arterial stiffness (AS) wgnas defined by the aortic PWV of >10 m/s. Results: The mean PVWs were 8.14 +/- 2.39 m/s the mean AIx was 21.23 +/- 11.58 m/s, and AS was 33.7% in hemodialysis patients. Systolic blood pressure, pulse rate, pulse pressure, central systolic blood pressure, older age, HD vintage, HT vintage, creatinine, CRP and neutrophil leukocyte ratio (NLR), were related factors with AS. Multivariate linear regression analysis showed that systolic blood pressure (beta=0.322; 95% CI: 0.007-0.042; p = 0.006), and age of patients (beta=0.787; 95% CI: 0.095-0.127; p<0.001) were independent determinants of PWVs. Conclusion: The frequency of AS was 33.7% in hemodialysis patients without a history of cardiovascular disease. Increased age and systolic blood pressure were independent factors affecting PWV. Effective blood pressure control therapy can reduce AS in hemodialysis patients.
Keywords: Pulse wave velocity; Arterial stiffness; Cardiovasculer disease; Systolic blood pressure; Hemodialysis